Recycled Rare Earth Ions From E-Waste In Borogermanate Glasses For Magneto-Optical Applications - Elisa Berno, Ana [UNESP]; Caixeta, Fábio J. [UNESP]; Ruzene, João Pedro C. [UNESP]; Feltran, Aline M. [UNESP]; Albino, Leonardo V. [UNESP]; Abuçafy, Marina P. [UNESP]; Silva, Otávio de B. [UNESP]; Rodrigues, João Pedro P. [UNESP]; P. Ferreira-Neto, Elias [UNESP]; Rosa, Amauri P. A.; Bevilaqua, Denise [UNESP]; Nalin, Marcelo [UNESP]; et al. (My University, 2025)
Magneto-optical borogermanate glasses were developed by incorporating electro-electronic waste recovered from fluorescent lamps. Glasses with a composition of (41GeO₂–25B₂O₃–4Al₂O₃–10Na₂O–20BaO)-x%wst, (x=0, 10, 20, 30, and 50 wt% of waste) were prepared. The final chemical composition was determined, and the glasses were characterized through thermal, structural, morphological, optical, and magneto-optical analyses. The addition of lamp waste to the glass matrix did not induce crystallization and stable glass materials were obtained, as confirmed by thermal analysis. Raman spectroscopy has shown that the addition of different amounts of waste into the vitreous matrix induces structural rearrangements as evidenced by the vibration bands of non-bridging B−O− bonds. Regarding optical properties, the transmittance of the glasses slightly decreased with waste incorporation. Photoluminescence showed electronic transitions attributed to the Tb3+ and Eu3+ ions and non-radiative energy transfer from the host to both Ln3+ ions and between them was observed. Finally, a Verdet constant value of −40.9 rad. T−1 m−1 at 632.8 nm was obtained, highlighting the potential of these sustainable glasses as Faraday rotators.
Keywords: e-waste; Magneto-optical glasses; rare earth ions